2019
DOI: 10.1021/acssuschemeng.9b02315
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Conducting Polymers: Toward Sustainable and Versatile Batteries

Abstract: Rapid growth of smart electronics and implantable medical devices markets has driven the development of next-generation sustainable, flexible, or implantable batteries. Conducting polymers with unique mechanical and electronic properties offer new possibilities and have attracted great attention. In this review, we discuss approaches used to tune conducting polymers at the molecular level for designated properties and applications such as improved electrochemical performance, and we discuss approaches used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 207 publications
0
66
0
Order By: Relevance
“…Since the discovery of conductive polymers, extensive research has been conducted on these fascinating polymers and it has been found that conductive polymers not only deliver comparable conductivity to semiconductors or metal conductors but also provide redox activity as electrode materials. [ 31 ] In 1981, Heeger and coworkers first utilized conductive polymers as the electrode materials for LIBs, which initiated a boom in the research of conductive polymers in the battery field. [ 32 ] The widely researched conductive polymer cathode materials include polyacetylene, [ 33 ] polyaniline, [ 34 ] polypyrrole, [ 35 ] polythiophene, [ 36 ] and polyphenylene, [ 37 ] as shown in Figure 1a.…”
Section: Conductive Polymersmentioning
confidence: 99%
“…Since the discovery of conductive polymers, extensive research has been conducted on these fascinating polymers and it has been found that conductive polymers not only deliver comparable conductivity to semiconductors or metal conductors but also provide redox activity as electrode materials. [ 31 ] In 1981, Heeger and coworkers first utilized conductive polymers as the electrode materials for LIBs, which initiated a boom in the research of conductive polymers in the battery field. [ 32 ] The widely researched conductive polymer cathode materials include polyacetylene, [ 33 ] polyaniline, [ 34 ] polypyrrole, [ 35 ] polythiophene, [ 36 ] and polyphenylene, [ 37 ] as shown in Figure 1a.…”
Section: Conductive Polymersmentioning
confidence: 99%
“…Different conjugated polymers such as polythiophene [ 2 , 3 ], polypyrrole (PPy) [ 4 , 5 ], poly(3,ethylenendioxythiophene) (PEDOT) [ 6 , 7 ], and polyaniline (PANI) [ 8 , 9 ], have been explored as engineering polymers (multifunctional materials). Among the CPs, PPy and PANI are considered favorable materials for multiple applications, such as capacitors, redox capacitors, lithium-ion batteries, super-condensers, filtering membranes, water treatment, and biosensors [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic electrode materials are characterized by relatively high theoretical capacity, moderate operating potentials, chemical diversity, and environmental friendliness, showing great potential [6] . Currently, the most widely studied organic electrode materials contain organic carbonyl compounds, [7] organic sulfides, [8] conductive polymers, [9] and organic radical polymers [10] . Organic carbonyl compounds with abundant functional groups are the most far‐ranging owing to high redox potential and fast reaction kinetics [11] .…”
Section: Introductionmentioning
confidence: 99%